2000
DOI: 10.1089/15209150050194215
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Effects on Glucose Measurements with a Reference Analyzer and Three Handheld Meters

Abstract: Oxygen may affect glucose meter and reference analyzer measurements. We evaluated the effects of changes in blood oxygen tension (Po2) on Accu-Chek Comfort Curve (Roche Diagnostics, Indianapolis, IN), Precision G, (Abbott Laboratories, Bedford, MA) and One Touch II (Lifescan, Milpitas, CA) glucose meter measurements, and on Yellow Springs Instruments (YSI) (Yellow Springs, OH) reference analyzer measurements. Venous blood drawn from healthy volunteers was adjusted to three glucose levels of 80, 200, and 400 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Several previous studies reported that some test strips, especially those with glucose oxidase enzyme reaction, are sensitive to oxygen and that high oxygen concentrations may lead to system results lower than the true value. [29][30][31][32][33] Most of the published system accuracy evaluation studies either do not evaluate samples with BG concentration <80 and ≥300 mg/dl (or not sufficient numbers) or use venous blood. [34][35][36][37][38][39] Main reasons for doing so are most likely the difficulty of designing a controlled human study or an adequate procedure to obtain capillary blood samples in hypoglycemic and hyperglycemic ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported that some test strips, especially those with glucose oxidase enzyme reaction, are sensitive to oxygen and that high oxygen concentrations may lead to system results lower than the true value. [29][30][31][32][33] Most of the published system accuracy evaluation studies either do not evaluate samples with BG concentration <80 and ≥300 mg/dl (or not sufficient numbers) or use venous blood. [34][35][36][37][38][39] Main reasons for doing so are most likely the difficulty of designing a controlled human study or an adequate procedure to obtain capillary blood samples in hypoglycemic and hyperglycemic ranges.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with several other studies reporting that some GOD systems underestimate BG values when measurements were performed on blood samples with increased pO 2 values. 8,9,11,21 In such studies, measurements on adjusted venous blood samples with pO 2 values >100 mm Hg or in critically ill patients/patients undergoing surgery with increased arterial pO 2 values up to approximately 600 mm Hg resulted in a negative bias. Probably, the competition between dissolved oxygen in the blood sample and the electron acceptor on the biosensor of test strips leads to a diminished chemical reaction when the blood samples' pO 2 value is increased.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] Point-of-care device test strips using glucose oxidase (see later) are prone to errors caused by oxygen effects. Tang and colleagues showed that errors of 15% or more could occur with highly oxygenated blood samples (i.e., PaO 2 >100 mm Hg), 44 and variances of up to 46% from reference values have been observed under hyperbaric conditions. [45][46][47][48] These devices have also been shown…”
Section: Terminologymentioning
confidence: 99%